Calotropis procera: A preliminary survey on its phytoextraction capabilities in Brazil - Newton PU Barbosa; Geraldo Wilson Fernandes; Uemura, George; Maria Ângela de BC Menezes; Ludmila VS Matos; Aparecida da Silva, Maria; Menezes, Rômulo SC; Almeida-Cortez, Jarcilene S (Neotropical biology and conservation, 2013)
Calotropis procera (Apocynaceae) is a non-native species that has its origin in Africa and Asia, but was introduced into the northeastern region of Brazil in the beginning of last century. In some areas, the dry biomass of C. procera is used as animal feed. However, previous studies indicated that the species is capable of accumulating many chemical elements. On the other hand, it could also mean that this species may be used for phytoremediation. Hence, we used neutron activation analysis, k0-method, to test the capability of the leaves of C. procera to accumulate trace elements. The study was carried out in two distinct areas (polluted and non-polluted) in the State of Pernambuco, Brazil. Our results indicate that new elements can be added to the list of elements taken up by C. procera, thus contributing to the understanding of the biology of this plant species as an accumulator of trace elements. Some elements, such as Ba and Sr, have higher concentrations in the non-polluted areas than in polluted areas. Thus, the presence of many trace elements in C. procera indicates that its use as animal feed should be viewed with extreme caution. However low levels of these trace elements in C. procera do not indicate that this species is a hyper-accumulator plant.